NArCoS: The new hodoscope for neutrons and charged particles - Pagano, E. V.; De Filippo, E.; Russotto, P.; Cardella, G.; Castoldi, A.; Geraci, E.; Gnoffo, B.; Guazzoni, C.; Lanzalone, G.; Maiolino, C.; Martorana, N. S.; Pagano, A.; et al. (Frontiers in Physics, 2023)
The proper detection of neutrons as well as charged particles, is motivated by the recent efforts to construct new facilities for Radioactive Ion Beams (RIBs) all over the world. Detection of neutrons represents an important opportunity to improve our understanding in nuclear spectroscopy and reaction dynamics, with the possibility to constrain theoretical models of the Nuclear Equation of State (NEoS) and to investigate in-medium nuclear interactions. This topic has also important implications in the study of astrophysical objects like neutron stars. In this work, the state of art of NArCoS (Neutron Array for Correlation Studies), a new hodoscope for neutron and charged particles under construction in Catania (INFN), is shortly reviewed.